Analisa Ketel Uap Pipa Air Pada Pabrik CPO - Lelawati lelawati (MAJALAH TEKNIK SIMES, 2020)
Abstract The oil palm processing industry in CPO mills really needs the role of a boiler, where the working process of a boiler is by heating water to boiling and producing high-pressure hot steam. Based on the fluid flowing in the pipe there are two kinds of boilers, fire tube boiler and water tube boiler. The difference between the two lies in the resulting steam pressure where the water pipe steam boiler is higher than the fire pipe boiler